PEMBAHARUAN HUKUM PERKAWINAN INDONESIA - yunanto, yananto (Fakultas Hukum, Universitas Diponegoro, 2018)
As a provision that will bring change, UUP No. 1 Year 1974 concerning Marriage (UUP) cannot be separated from weaknesses. In its implementation, UUP will also clash with the previous social value which results in pros and cons. This shows that UUP is more a political product that is applied in the reality of diversity. The weaknesses and pros and cons of the substance of UUP lead to the realization of renewal in the field of marriage law. However, it is also realized to realize this is not easy because the field of marriage is one of the fields of civilization that has sensitive and conflict characteristics. Keywords: renewal, marriage law.